Solid phase extraction of β-sitosterol and α-tocopherol from sunflower oil deodorizer distillate using desilicated zeolite - Karaoglu, O.; Alpdogan, G.; Ozdemir, I. S.; Ertas, E. (CONSEJO SUPERIOR INVESTIGACIONES CIENTIFICAS-CSIC, 2020)
In this study, the efficiency of using zeolite-based adsorbents in a solid phase extraction (SPE) procedure of alpha-tocopherol and beta-sitosterol isolation from Sunflower Oil Deodorizer Distillate (SuDOD) without pre-treatment was investigated. The results showed that 99.2% a-tocopherol and 97.3% beta-sitosterol were successfully isolated as pure fractions from SuDOD, when desilicated ZSM-5-type zeolite (DSiZSM-5) was used as adsorbent on a SPE. A simple and rapid HPLC method for simultaneous alpha-tocopherol and beta-sitosterol analysis was developed and validated according to AOAC guidelines. It was found that the inclusion of a DSiZSM-5 SPE step increased the precision of the alpha-tocopherol and beta-sitosterol analysis. In conclusion, DSiZSM-5 zeolite was proven to be an efficient adsorbent which can be used not only for the recovery of alpha-tocopherol and beta-sitosterol from SuDOD in industrial scale, but also in a laboratory scale clean-up method prior to the analysis of alpha-tocopherol and beta-sitosterol.
Keywords: SPE; Sterol; Sunflower oil deodorizer distillate; Tocopherol; Zeolite; Chemistry; Food Science & Technology